The contribution of ecological design to green planning approach of a university campus in Malaysia - Asmawi, M. Zainora; Abdul Aziz, Abdul Razak (2011)
The concept of ecological design has produced positive results in terms of supporting the achievement of sustainable development in many fields. However, its practice currently faces many challenges due to many influential factors such as the low level of acceptance amongst stakeholders. As such, this research attempts to study the application of ecological design in contributing to the approach of green planning in designing a university campus in Serdang, Selangor. The researcher had made an observation survey of 23 selected buildings within the Universiti Putra Malaysia area, based on a set of pre-determined factors and its sub-factors in determining the level of compliance to ecological design. Generally, the results demonstrated that the level was relatively moderate and many buildings failed to comply with some factors of ecological design. The reason being that the buildings were built more than 10 years ago in which the concept of ecological design was rather new at that time. Some newer buildings corresponded fairly well to some ecological design, such as the elements of indoor environmental quality.